Alteration of a protease-sensitive region of Pseudomonas exotoxin prolongs its survival in the circulation of mice. - Brinkmann, U (1992)
Pseudomonas exotoxin A (PE) is a single-chain 66-kDa polypeptide that kills eukaryotic cells by ADP-ribosylation of translational elongation factor 2. PE is composed of three major structural domains whose functions are binding of cells (I), translocation (II), and ADP-ribosylation (III). Here we describe a protease cleavage target that is located near arginine-490 on the surface of domain III. We made several different types of mutations near arginine-490. Deletion of arginine-490 or replacement of arginine-490 and -492 with serine and lysine or with two lysines resulted in protease-resistant molecules that were fully cytotoxic and had normal ADP-ribosylation activity. However, the half-life in mouse blood of the PE delta 490 mutant was 24 min whereas that of PE was 13 min. Furthermore, two PE mutants that were protease-hypersensitive, PEGlu246,247,249 and PEGlu57,246,247,249 (in which glutamate residues replace basic residues at the indicated positions), had very short half-lives. These data indicate that protease sensitivity is an important determinant in the half-life of PE in the circulation and suggest that the half-life of other proteins may be prolonged by removal of protease sites. Deletion of arginine-492 or the replacement of amino acids 486-491 with three glycines markedly diminished ADP-ribosylation activity and cytotoxicity, indicating that this region of domain III is also important for catalytic activity.